2015
DOI: 10.1053/j.gastro.2015.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β Signaling in Colorectal Cancer Cells With Microsatellite Instability Despite Biallelic Mutations in TGFBR2

Abstract: TGFβ signaling remains active in some MSI-H CRC cells despite the presence of frameshift mutations in the TGFBR2 gene because the mutated gene still expresses a functional protein. Strategies to reactivate TGFβ signaling in colorectal tumors might not be warranted, and the functional effects of mutations at other regions of microsatellite instability should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…TβRII and ACVR2A, another TGF-β component, were found to be the most frequently mutated genes in MSI-H CRC from patients with Lynch syndrome [74]. A recently published paper has shown that TGF-β signaling may still remain active in some MSI-H CRC cells despite the presence of frameshift mutations in the TβRII gene [75]. The exact mechanism of the contribution of TβRII mutations to CRC is still not known.…”
Section: Tgf-β In Colorectal Cancermentioning
confidence: 99%
“…TβRII and ACVR2A, another TGF-β component, were found to be the most frequently mutated genes in MSI-H CRC from patients with Lynch syndrome [74]. A recently published paper has shown that TGF-β signaling may still remain active in some MSI-H CRC cells despite the presence of frameshift mutations in the TβRII gene [75]. The exact mechanism of the contribution of TβRII mutations to CRC is still not known.…”
Section: Tgf-β In Colorectal Cancermentioning
confidence: 99%
“…TGFβR2 binds to TGFβ, which may further phosphorylate proteins, and then enters the nucleus to regulate the gene transcription (18). Mutations in TGFβR2 have been implicated in human cancer (19,20). A study by Zhang et al (21) reported that mRNA and protein expression levels of TGFβR2 were significantly lower in NPC tissues compared with the non-cancerous tissues, and EBV encoded small RNA hybridization signals in NPC demonstrated significant associations with TGFβR2 (21).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of TGFBR2 expression enables cancer cells to escape the growth inhibitory effect of TGF-β and may cause loss of cell growth regulation. Several studies have discussed the potential mechanisms of the dysregulation of TGFBR2 [22, 23]. However, other latent mechanisms require further exploration for the clarification of the specific functions of TGFBR2 in carcinogenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 99%